Effect of Strain Rate on Hot Ductility of a Duplex Stainless Steel - Zhenhua Wang; Wenyuan Ma; Chengming Wang (Advances in Materials Science and Engineering)
Duplex stainless steels (DSSs) often have bad hot workability. In this study, specimens of 2205 DSS were hot tensioned over a strain rate range from 0.005 s–1 to 50 s–1 to examine the hot ductility. The crack morphology was observed, and the dependence of hot ductility on the strain rate was analyzed. From 0.005 s–1 to 0.5 s–1, both the total elongation and the reduction in area increased with the strain rate. The reduction in area exhibited a small decrease when the strain rate was greater than 0.5 s–1. More than 85% of cracks formed between the ferrite and austenite, and no less than 70% of crack tips propagated between the ferrite and austenite. When the strain rate was increased from 0.005 s–1 to 0.5 s–1, dynamic recrystallization was promoted in the austenite, and the number fraction of low-angle grain boundaries in the ferrite was improved. The higher strain rate reduced the difference between ferrite and austenite in hardness, which improved the hot ductility. For 2205 DDS, the suggested strain rate is 0.5 s–1 and above to avoid surface and edge cracking during hot forging or hot rolling. The findings will be of value for the understanding of hot ductility of DSSs and other dual-phase alloys.